Production, Purification and Characterization of Cellulose from Local Isolate of Pantoea spp - L. Atala, Mohmmed; M. Jasim, Hameed; M. Ibrahim, Kadhim (Iraqi Journal of Science, 2023)
Soil samples from fields cultivated with barley and wheat in addition to samplesfrom spoiled orange and apple fruits and carrot roots were collected with the aim toisolate cellulase producing bacterial strains. Bacterial isolates obtained from thesesamples were grown on a selective medium containing carboxymethyl cellulose(CMC) as a sole source for carbon and energy. Results showed that nine isolates outof fifty were able to produce cellulase.The specific activity of cellulase in culturefiltrate of the most efficient isolate was 1.601 u/mg protein.This isolate wasidentified according to its morphological characteristics and biochemical tests, andthen by using Api 20-E and VITEK-II identification systems and was identified asPantoea dispersa. Cellulase produced by P. dispersa was purified throughout fourpurification steps including ammonium sulfate precipitation, dialysis followed bypurification with ion exchange chromatography using DEAE-cellulose, and then gelfiltration throughout sephadex-G200. Purification results showed that the specificactivity of the purified enzyme was 1181.8 u/mg protein with a purification fold andyield 115.2 and 26.6% respectively. Purified cellulase from Pantoea dispersa waswell characterized by studying some enzyme characteristics. The molecular weightof cellulase was 15148 dalton, and pH 7.0 was the optimum for enzyme activity andstability, while 30 ºC was the optimum for enzyme activity and stability